Colloidal Stability and In-Vitro and In-Vivo Biocompatibility of Gd-Doped batio3 Nanoparticles Coated with Poly(Ethylene Glycol) - Leon, J; Leon, J (Elsevier B.V., 2026)
Nanoparticle-based technologies in biomedicine require the precise design of hybrid systems to enhance stability, safety, and diagnostic performance. Conventional magnetic resonance imaging (MRI) contrast agents often face limitations such as metal ion release, tissue accumulation, and magnetic field distortions that compromise image quality and biosafety. In this study, we synthesized gadolinium-doped barium titanate (BTO:Gd) nanoparticles that integrate the ferroelectric characteristics of BTO with the paramagnetic properties of Gd3+, providing a multifunctional platform for biomedical imaging and a potential alternative to conventional MRI contrast agents. BTO nanoparticles were doped with Gd (1–5 mol%), via a sol–gel–hydrothermal method and subsequently coated with polyethylene glycol (PEG) to improve biocompatibility and colloidal stability. Structural and surface characteristics (XRD, SEM, FTIR, Raman spectroscopy, and zeta potential) confirmed the formation of a cubic perovskite structure, particle sizes below 60 nm, and enhanced colloidal stability (ζ = −27 to −33 mV, pH 6–8), supporting stable dispersion. Moreover, Gd doping increased the ferrimagnetic and paramagnetic responses of the BTO nanoparticles while reducing diamagnetism, thereby rendering them suitable for MRI contrast enhancement. In vitro assays using HEK293 cells exposed to BTO:Gd and (BTO:Gd)–PEG nanoparticles indicated no significant cytotoxicity or elevated ROS and NO generation. In vivo studies with Drosophila melanogaster further demonstrated that PEGylation effectively mitigated developmental toxicity, improving viability from 60.45 % (uncoated) to 97.24 % (PEG-coated). Overall, PEGylated BTO:Gd nanoparticles exhibited superior stability, magnetic responsiveness, and biocompatibility, underscoring their potential as safe and effective candidates for biomedical imaging applications. © 2025 The Authors